IN THE HADITHS OF IMAM BUKHARY: ATTITUDE TO MOTHER AND WIFE - Matluba Tokhtaeva (Journals Park Publishing, 2023)
In the article, in the Islamic religion, all people, regardless of their gender, have equal rights before God, in the sources of the Islamic religion, a woman is, first of all, the pillar or the main foundation of spirituality and education, especially the figure of the mother is always considered the most honorable person in the eyes and thinking of mankind, national and universal. one of the values is the mother's duty to the child and the greatness of the woman's responsibility to the family, Imam Bukhari's hadiths have studied the great educational importance of mother-woman relations.